The Perception of Teacher and Student on Poster Use in Islamic Center Senior High School - Amaruddin, Muhammad; Saifulloh, Ahmad Iklil; Lindawati, Rini (PT. Kreasi Karya Majakata, 2024)
This study examined the perceptions of teachers and students regarding the use of posters as a teaching tool at Islamic Center Senior High School. This research aimed to know teachers and students perception on poster use in teaching public speaking. This research respondents was the second grade class of Islamic Center Senior High School. This study instrument used interview for gathering data. This research used qualitative analysis with descriptive qualitative approach, the findings reveal that posters are positively viewed by both teachers and students deep perception, as they enhance effectiveness and retention. This study underscored the significance of how effective responsive visual aids in improving public speaking skills. This research addressed the challenges of teaching and learning English public speaking in an EFL context, focusing on students' fear, discomfort, and pronunciation issues, and proposed using digital posters as a tool to improve their public speaking skills and instill important values.